2355. Clinically vs. Serologically Identified Varicella: A Hidden Infection Burden. Lessons of 10-Year Follow-up in Varicella Endemic Countries. (26th November 2018) - Gillard, Paul; Povey, Michael; Carryn, Stephane
Abstract: Background: A randomized, controlled, long-term varicella vaccine efficacy study (NCT00226499) was conducted in several European countries with no universal varicella vaccination. The control group allows studying the immunological response profiles to natural varicella exposure and disease in children from 1 year of age onwards. Methods: Of 5, 803 subjects enrolled in the study, 744 were vaccinated with 2 doses of measles-mumps-rubella vaccine as active control. Follow-up lasted for up to 10 years. Varicella case ascertainment was done by combining PCR testing of skin lesions, epidemiological context and blinded clinical case adjudication by independent experts. A confirmed case required a positive PCR result or a positive epidemiological context with a positive case adjudication. Results: In the control group, a total of 352 confirmed varicella episodes were captured; of which, 339 had an available serum sample taken before and after the episode at any of the year 1 or bi-yearly visits scheduled per protocol. All subjects were seronegative for anti-VZV antibodies before vaccination. The immunological profile showed that 96% of subjects with varicella episodes experienced an 8-fold increase of the anti-VZV titers when comparing the sample available after the episode vs. the one before the episode. The data indicate that the GMC levels were similar to that induced by 2-dose immunization with varicella vaccines, and persisted over many years after the varicella episode without indication of waning (figure). In subjects without any reported varicella episode, 8-fold increases of the anti-VZV titers between 2 successive blood samples were measured in up to 34% of consecutive pairs of serum samples. Conclusion: To our knowledge, this is the first long-term analysis of the immunological history of anti-varicella immunological profile in young children exposed to a high varicella force of infection. About one-third of subjects not vaccinated against varicella developed an anti-VZV immune response although no varicella disease was reported. Sub-clinical varicella may occur more frequently than anticipated. The total incidence of varicella infections might be under-estimated by syndromic surveys only. Funding: GlaxoSmithKline Biologicals SA. Disclosures: P. Gillard, GSK: Employee and Shareholder, Salary. M. Povey, GSK: Employee, Salary. S. Carryn, GSK: Employee and Shareholder, Restricted shares, and Salary.